Промоакційний маркетинг: міф просування чи технологія конкурентної боротьби? Соціологічна концептуалізація крізь призму соціально-конструктивістського підходу - Нечітайло, І. С.; Nechitailo, I. S.; ORCID: https://orcid.org/0000-0002-0656-0370; Хижняк, Д. І.; Khyzhniak, D. I. (Габітус. - 2023. - Вип. 45. - С. 28-34, 2023)
Розкрито сутність інструментів промоакційного маркетингу крізь призму соціології, зокрема з позиції соціально-конструктивістського підходу. Виявлено низку символічних прийомів, які використовують промоутери як головні актори промоакційного маркетингу. Підкреслено, що детермінація споживацького вибору є, по суті, процесом цілеспрямованого утворення таких (об’єктивних) умов, щоб викликати певну (суб’єктивну) реакцію споживача на рівні латентних складників соціальної дії. Дії промоутерів є, по суті, актами соціального конструювання реальності (для) споживача, у яких останній є повноцінним суб’єктом, що підкреслює позитивну функцію та результати міфотворчої діяльності промоакційного маркетингу, яка є необхідною для привернення уваги споживача і ефективної конкурентної боротьби.

The article is devoted to consideration of promotional marketing as a technology for the use of special tools designed to influence people’s consumer behavior. Attention is drawn to the fact that, both at the level of mass consciousness and in scientific discourse, there is a contradiction regarding the interpretation of the nature of such influence: on the one hand, it is considered manipulative, and therefore negative; on the other hand, promotional marketing is considered as a completely normal phenomenon of modern society, connected with the need to satisfy the real needs of consumers by providing them with detailed information about this or that product. Thus, the purpose of the article is to reveal the essence of promotional marketing tools through the prism of sociology, in particular, from the standpoint of a social constructivist approach (as constructing social reality (for) a potential consumer). The results of the research conducted by the authors using qualitative methodology (in-depth interview, focused group interview, included observation) are presented. A number of symbolic techniques used by promoters as the main actors of promotional marketing have been identified: 1) “Kindness”; 2) “Do like everyone”; 3) “Game on contrast”; 4) “Sequence effect”; 5) “Effect of scarcity”; 6) “Price – quality”. It is concluded that the determination of consumer choice is, in fact, a process of purposeful formation of such (objective) conditions to cause a certain (subjective) reaction of the consumer at the level of latent components of social action. The promoters’ activities are in fact acts of social construction of reality (for) the consumer, in which consumer is a full-fledged subject, which emphasizes the positive function and results of the myth-making activity of promotional marketing, which is necessary for attracting the consumers’ attention and effective competition.

Раскрыта сущность инструментов промоакционного маркетинга через призму социологии, в том числе с позиции социально-конструктивистского подхода. Выявлен ряд символических приемов, которые используют промоутеры в качестве главных актеров промоакционного маркетинга. Подчеркнуто, что детерминация потребительского выбора является по сути процессом целенаправленного образования таких (объективных) условий, чтобы вызвать определенную (субъективную) реакцию потребителя на уровне латентных составляющих социального действия. Действия промоутеров являются, по сути, актами социального конструирования реальности (для) потребителя, в которых последний является полноценным субъектом, подчеркивающим положительную функцию и результаты мифотворческой деятельности промоакционного маркетинга, необходимой для привлечения внимания потребителя и эффективной конкурентной борьбы.
Promotional marketing: myth of promotion or technology of competitive struggle? Sociological conceptualization through the prism of the social-constructivist approach
Нечітайло, І. С. Промоакційний маркетинг: міф просування чи технологія конкурентної боротьби? Соціологічна концептуалізація крізь призму соціально-конструктивістського підходу / Нечітайло І. С., Хижняк Д. І. // Габітус. - 2023. - Вип. 45. - С. 28-34. - DOI: https://doi.org/ 10.32782/2663-5208.2023.45.4.
Keywords: Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; Психологія. Рsychology. Психология; Україна. Ukraine. Украина; промоакційний маркетинг; promotional marketing; промоакционный маркетинг; соціально-конструктивістський підхід; social constructivist approach; социально-конструктивистский подход; споживач; consumer; потребитель; детермінація споживацької поведінки; determination of consumer behavior; детерминация потребительского поведения; соціальна дія; social action; социальное действие